Developmental effects of the industrial cooling water additives morpholine and sodium hypochlorite on lake whitefish (Coregonus clupeaformis). (31st January 2017) - Thome, Christopher; Mitz, Charlotte; Sreetharan, Shayenthiran; Mitz, Charles; Somers, Christopher M.; Manzon, Richard G.; Boreham, Douglas R.; Wilson, Joanna Y.
Abstract: Chemicals used in the prevention of corrosion and biofouling may be released into the environment via industrial cooling water discharges. The authors assessed the impacts of 2 commonly used chemicals, morpholine and sodium hypochlorite, on development in lake whitefish ( Coregonus clupeaformis ). Embryos were exposed chronically, beginning at fertilization or at the eyed stage. Acute 96‐h exposures were also examined at 4 development stages. Chronic morpholine resulted in median lethal concentrations (LC50s) of 219 ± 54 mg/L when exposure began at fertilization and 674 ± 12 mg/L when exposure began at the eyed stage, suggesting that embryos are more sensitive earlier in development. Chronic morpholine exposure advanced hatching by up to 30%, and the early hatching embryos were up to 10% smaller in body length. A decrease in yolk conversion efficiency was also observed in embryos exposed to chronic morpholine concentrations of 1000 mg/L. The majority of effects from morpholine exposure manifested near hatch, possibly reflecting changes in chorion permeability at the end of embryonic development. Sodium hypochlorite only impacted survival with chronic exposure from fertilization, where the total residual chlorine LC50 was 0.52 ± 0.11 mg/L. Acute exposures to both chemicals had minimal effects up to the highest tested concentrations. Overall, the results suggest that the risk during development from exposure to morpholine and sodium hypochlorite is low under normal operating conditions. Environ Toxicol Chem 2017;36:1955–1965. © 2016 SETAC